The Evil Princess vs. the Brave Knight - Holm, Jennifer L; Holm, Matthew (Random House, 2019)
Meet the Evil Princess and the Brave Knight. She casts terrible spells, while he fights dragons. He rescues cats in distress, while she makes mischief. No wonder there isn't much peace in this kingdom! But is the Evil Princess really so evil? And is the Brave Knight truly as chivalrous as he seems?